2005
DOI: 10.1002/ccd.20332
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of oral sirolimus to inhibit in‐stent intimal hyperplasia

Abstract: Sirolimus systemic administration has shown marked inhibition of neointimal hyperplasia (NIH) after balloon angioplasty in porcine models. In this pilot study, we tested the hypothesis that oral sirolimus is safe and effective to inhibit in-stent NIH and therefore to prevent and treat in-stent restenosis (ISR). Twelve patients (18 lesions) with high risk for ISR, including 8 ISR lesions, were admitted. One day before the procedure, patients were given a 15 mg loading dose of oral sirolimus, followed by 5 mg da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 24 publications
2
15
0
1
Order By: Relevance
“…These new devices are associated with a dramatic and sustained reduction of the restenosis process, as can be observed from several clinical trials (6,14,15). In another field of application, oral administration of rapamycin has been proposed as an alternative to drug-eluting stents for preventing in-stent restenosis after percutaneous coronary intervention (9,16,17). However, it is important to establish other benefits of rapamycin, including the regression of atherosclerosis that affects mainly large conductance vessels and the control of the circulation that is mainly exerted by resistance vessels, as well as to address concerns regarding toxicity and late adverse side effects (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These new devices are associated with a dramatic and sustained reduction of the restenosis process, as can be observed from several clinical trials (6,14,15). In another field of application, oral administration of rapamycin has been proposed as an alternative to drug-eluting stents for preventing in-stent restenosis after percutaneous coronary intervention (9,16,17). However, it is important to establish other benefits of rapamycin, including the regression of atherosclerosis that affects mainly large conductance vessels and the control of the circulation that is mainly exerted by resistance vessels, as well as to address concerns regarding toxicity and late adverse side effects (14).…”
Section: Discussionmentioning
confidence: 99%
“…Oral administration of rapamycin has been proposed as an alternative to drug-eluting stents, especially when multiple stenting is recommended (9), thus raising the necessity to investigate the potential effects of this agent on the vessels. Focusing on this issue, Milliard et al (10) showed that systemic treatment with rapamycin (2 mg/kg) for 2 weeks attenuated the vasoconstriction and potentiated the endothelium-dependent vasorelaxation of aortic rings in Sprague-Dawley rats.…”
Section: Introductionmentioning
confidence: 99%
“…This sample size is sufficient to detect a difference of at least 17.3% in the mean neointimal obstruction (75% reduction of the expected value for controls 13 ), with the possibility for multiple comparisons between all groups, assuming a common standard deviation of 10%, with a significance level (alpha) of 0.05 and power (beta) of 80%, considering an attrition rate of 20% 8 .…”
Section: Cost-effectivenessmentioning
confidence: 99%
“…Despite having studied highly heterogeneous patient groups and drug regimens, these studies have shown a significant reduction of angiographic ISR (12)(13)(14)(15). The aim of the present study was to characterize the systemic response of biomarkers known to be involved in the vascular response to coronary stenting and determine if oral sirolimus has any effect on the behavior of these biomarkers.…”
mentioning
confidence: 99%